1992
DOI: 10.1007/bf00232421
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of black pepper (Piper nigrum Linn.) through shoot tip cultures

Abstract: The morphogenetic potential of shoot tip explants of black pepper (Piper nigrum) was investigated and an effective multiple-shoot propagation method is described. Various combinations of media, growth regulators and sterilization treatments were compared. Problems with establishment in tissue culture sometimes occurred, probably caused by endogenous pathogens associated with tissue exudates. The best establishment and proliferation of shoot tip explants was obtained on MS medium containing 1.5 mg l(-1) BAP alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 1 publication
5
33
0
4
Order By: Relevance
“…Deshpande et al (1998) indicated that a low concentration of cytokinins in combination with AS favors multiple shoot induction in Ficus religiosa. In black pepper (Piper nigrum), Philip et al (1992) reported that AS increased the number of shoot buds per regenerating explant.…”
Section: Discussionmentioning
confidence: 99%
“…Deshpande et al (1998) indicated that a low concentration of cytokinins in combination with AS favors multiple shoot induction in Ficus religiosa. In black pepper (Piper nigrum), Philip et al (1992) reported that AS increased the number of shoot buds per regenerating explant.…”
Section: Discussionmentioning
confidence: 99%
“…PHILIP et al (1992) também obtiveram a multiplicação in vitro de pimenta-do-reino a partir de ápices caulinares de plantas adultas. Um dos problemas em obterem-se protocolos de regeneração in vitro a partir de plantas adultas é o controle das taxas de contaminação vindas do campo.…”
Section: Resultsunclassified
“…Isso confirma que concentrações menores de BAP são mais eficientes na indução de brotações e formação de explantes para "Bragantina". Entretanto, isso parece ser variável entre os genótipos de pimenta-do-reino, já que PHILIP et al (1992) verificaram que a concentração de 1,5mg L -1 foi mais eficiente que concentrações mais baixas de BAP na indução de brotos de pimenta-do-reino de uma variedade indiana.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…18 Nevertheless, the establishment of cell suspension cultures and investigation of associated secondary metabolism in Piperaceae species have so far remained untouched. Previous analysis of leaves of P. crassinervium have showed the occurrence of antifungal flavanones, benzoic acids and prenylated hydroquinones.…”
Section: Introductionmentioning
confidence: 99%